2000
DOI: 10.1021/jf9909104
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Analysis of Cotton Defoliant, Herbicide, and Insecticide Residues in Water by Solid-Phase Extraction and GC−NPD, GC−MS, and HPLC−Diode Array Detection

Abstract: A multiresidue procedure was developed for analysis of cotton pesticide and harvest-aid chemicals in water using solid-phase extraction and analysis by GC-NPD, GC-MS, and HPLC-DAD. Target compounds included the defoliants tribufos, dimethipin, thidiazuron; the herbicide diuron; and the insecticide methyl parathion. Three solid-phase extraction (SPE) media, octadecylsilyl (ODS), graphitized carbon black (GCB), and a divinylbenzene-N-vinyl pyrollidine copolymer (DVBVP), were evaluated. On GCB and ODS, recoveries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
2
18
0
1
Order By: Relevance
“…The same optimization steps mentioned above were used and the parameters a, b, a, and b were set to 0.03, 0.001, 0.05, and 20.19, respectively. The LOD and LOQ were estimated to be 2.5 and 10 ng/l, respectively, which were much lower than the values reported in the literatures (Potter et al 2000(Potter et al , 2003Li et al 2001) and satisfied the detection limit requirement of the European Union. The chromatograms obtained by LSRA with the originals at the concentrations of 10, 30, 40, 50, 60, 80, and 100 ng/l are compared in Fig.…”
Section: Lsra Applied To Spe-hplc Analysismentioning
confidence: 43%
See 1 more Smart Citation
“…The same optimization steps mentioned above were used and the parameters a, b, a, and b were set to 0.03, 0.001, 0.05, and 20.19, respectively. The LOD and LOQ were estimated to be 2.5 and 10 ng/l, respectively, which were much lower than the values reported in the literatures (Potter et al 2000(Potter et al , 2003Li et al 2001) and satisfied the detection limit requirement of the European Union. The chromatograms obtained by LSRA with the originals at the concentrations of 10, 30, 40, 50, 60, 80, and 100 ng/l are compared in Fig.…”
Section: Lsra Applied To Spe-hplc Analysismentioning
confidence: 43%
“…It means that an analytical method should reach a detection limit lower than around four times this value in order to reduce the possibility of false positive findings (LeConseil 1998). Potter et al (2000Potter et al ( , 2003 reported the method detection limit of thidiazuron at the exact 0.1 mg/l using solid phase extraction (SPE) and HPLC-diode array detection (HPLC-DAD), but the same method failed to achieve that concentration level in the research work of Li et al (2001). To our knowledge, there has not been any better result reported for residue analysis of thidiazuron in water.…”
Section: Introductionmentioning
confidence: 99%
“…특히, thidiazuron은 purine계 합성생장 조정제보다도 더 생리 활성이 더 강한 것으로 알려져 있으며, 여러 목본성 식물 증식에도 사용되고 있다 (Green, 1994; Open Access Research Article Arndt and Rusch, 1985). Thidiazuron 분석법 연구에 대한 보고로 물, 토양 등 환 경매체에 대한 잔류분석과 (Potter et al, 2000;Guo et al, 2010), 목화씨 (Cai et al, 2009;Guo et al, 2005), 멜론 (Wang et al, 2010) (Fig. 4.).…”
Section: 서 론unclassified
“…Previous studies have shown bifenthrin to be toxic to D. magna (96-h LC50 ¼ 0.32 À 1.60 mg/L) [20,21]. Tribufos is a cotton defoliant used in agricultural areas in the Mississippi alluvial plain, the southeastern United States, Texas, California [21], and Georgia [22]. It is a cholinesterase inhibitor and has been shown to be toxic to D. magna (48-h LC50 ¼ 6.8 À 110.0 mg/L) [21].…”
Section: Chemicalsmentioning
confidence: 99%